Availability and Performance Analysis of Cloud Services - Callou, Gustavo; Vieira, Marco (Anais do Latin-American Symposium on Dependable Computing (LADC), 2024)
Companies need to adjust their service infrastructure to the demand over time. Given its elasticity and scalability, cloud computing represents an interesting option for meeting such demands. In this context, availability and performance are two critical aspects of cloud services that can significantly impact the success of businesses and organizations. This work proposes models to analyze availability and performance metrics of a web service hosted in a private cloud environment. Models based on stochastic Petri net and reliability block diagrams are proposed and validated through a testbed cloud service. The case studies illustrate the applicability of the proposed models, and the results clearly show the relevance of adopting models to represent cloud service systems.